Hubungan Pengetahuan dan Sikap dengan Perilaku Penggunaan Antibiotika (Studi pada kader Poslit AMIRA Boyolali) - Sutiningsih, Dwi (Jurnal Epidemiologi Kesehatan Komunitas, 2024)
Background: Antibiotics are used in phytosanitary care, fish farming, and as veterinary drugs, where they can also be used as preventative or curative treatments in livestock management. Inappropriate dosage and/or inappropriate use of antibiotics can result in residues. The purpose of this study was to determine the relationship between knowledge and attitudes of AMIRA postlit cadres regarding antibiotic use in livestock.Methods: This study is an analytical observational study with a cross-sectional design. The population in this study were all AMIRA Poslit cadres, totaling 55 respondents. The bivariate analysis used was the Chi-Square test to analyze the relationship between respondents' knowledge and attitudes with antibiotic use behavior.Result: A total of 92.7% of respondents had a good level of knowledge, while the remaining 7.3% of respondents had a poor level of knowledge in the use of antibiotics. A total of 49.1% of respondents had a good attitude while the remaining 50.9% of respondents had a bad attitude. 50.9% of respondents had a supportive attitude, while the remaining 49.1% of respondents had an unsupportive attitude. There was no relationship between respondents' knowledge and antibiotic use behavior (p = 0.282), while respondents' attitudes were related to antibiotic use behavior in livestock (p = 0.005).Conclusion : The knowledge of AMIRA Poslit cadres is not related to the behavior of antibiotic use in livestock farming, while the cadres' attitudes are related.